Long-term associations between objective sleep quality and quantity and verbal memory performance in normal cognition and mild cognitive impairment - Skourti, Eleni; Simos, Panagiotis; Zampetakis, Alexandros; Koutentaki, Eirini; Zaganas, Ioannis; Alexopoulou, Christina; Vgontzas, Alexandros; Basta, Maria (Frontiers in Neuroscience, 2023)
Although the link between sleepand memory function is well established, associations between sleep macrostructure and memory function in normal cognition and Mild Cognitive Impairment remain unclear. We aimed to investigate the longitudinal associations of baseline objectively assessed sleep quality and duration, as well as time in bed, with verbal memory capacity over a 7-9 year period in a well-characterized subsample of 148 persons (mean age at baseline:72.8±6.7 years) from the Cretan Aging Cohort. Based on comprehensive neuropsychiatric and neuropsychological evaluation at baseline, participants were diagnosed with Mild Cognitive Impairment (MCI; n=79) or found to be cognitively unimpaired (CNI; n=69). Sleep quality/quantity was estimated from a 3-day consecutive actigraphy recording, whereas verbal memory capacity was examined using the Rey Auditory Verbal Learning Test (RAVLT) and the Greek Passage Memory Test at baseline and follow-up. Panel models were applied to the data using AMOS including several sociodemographic and clinical 2 This is a provisional file, not the final typeset article covariates. Sleep efficiency at baseline directly predicted subsequent memory performance in the total group (immediate passage recall: β=0.266, p=0.001; immediate word list recall:β=0.172, p=0.01;delayed passage retrieval:β=0.214, p=0.002) with the effects in Passage Memory reaching significance in both clinical groups. Wake after sleep onset time directly predicted follow-up immediate passage recall in the total sample (β=-0.211, p=0.001) and in the MCI group (β=-0.235, p=0.02). In the total sample, longer 24-hour sleep duration was associated with reduced memory performance indirectly through increased sleep duration at follow-up (immediate passage recall:β=-0.045, p=0.01; passage retention index:β=-0.051, p=0.01; RAVLT-delayed recall:β=-0.048, p=0.009;RAVLT-retention index:β= -0.066, p=0.004). Similar indirect effects were found for baseline 24-hour time in bed. Indirect effects of sleep duration/time in bed were found predominantly in the MCI group. Findings corroborate and expand previous work suggesting that poor sleep quality and long sleep duration predict worse memory function in elderly. Timely interventions to improve sleep could help prevent or delay age-related memory decline among non-demented elderly.